PEMIKIRAN PENDIDIKAN AGAMA (Studi Pemikiran Imam Al-Ghazali Dan Syed Muhammad Nauqib Al-Athas) - Suhada, Dodo (Jurnal Tawadhu, 2020)
Education is a learning process carried out for students so that they have a good understanding and understanding of something and later grow into a person who likes to think critically and become better, both in terms of affective, cognitive and psychomotor. Religion is an organized collection of beliefs, cultural systems, and worldviews that connect humans to the orders / orders of life.Many religions have narratives, symbols, and sacred histories intended to explain the meaning of life and / or explain the origin of life or the universe. From their beliefs about the cosmos and human nature, people derive morality, ethics, religious law or a preferred lifestyle. Religious practices can also include rituals, sermons, memorials or worship of gods, gods or goddesses, sacrifices, festivals, parties, trances, initiation, funeral services, wedding services, meditation, prayer, music, art, dance, community service or any other aspect of human culture. Religion may also contain mythology. Religious education is a key that cannot be ignored because religious education is one of the supporting factors in moral education. Humans who have faith and devotion to God cannot come into being suddenly, but through a long and long educational process. The educational process lasts for a lifetime both in the family, school, and community. The school environment itself is a good place for us to explore religious knowledge, because it is in the school environment that we can receive education that can affect the development of a human personality. Talk about religious education too, from time to time religious education has no change. The point of not having a change here is that religious education remains as it was in the beginning. In this case also the development of the era / era here, we need to know from it. This will make the way of thinking in the religious process not narrow and will always develop from both classical and modern philosophical thoughts.